Blue Management Accounting: Water Footprint, Cost, Efficiency, and Internal Control at WKP Corporation Headquarters - Chandra, Teddy; Renaldo, Nicholas; Chandra, Stefani; Ng, Martha (Journal of Environmental Accounting and Management, 2026)
Water is an important natural resource for living things, which needs a proper management system to avoid water scarcity. This study aims to analyze the application of Blue Management Accounting (BMA) at WKP Corporation Headquarters in Indonesia. A qualitative as well as quantitative research approach has been utilized to assess the water footprint, cost, efficiency, savings, and internal controls. The results showed that the water footprint is in accordance with the standard of healthy living. The water cost is still reasonable, and water efficiency is almost achievable and maintained by the company. However, water savings have not been running well, and internal water control has not worked well. This further reflects that, although overall, the implementation of BMA at WKP Corporation Headquarters has not been completely fulfilled, however, efforts made to improve water efficiency. The results also showed that there had been a change in water use that has increased since the COVID-19 pandemic entered Riau Province. Recommendations for the company are to maintain efficient use of water because it is directly related to costs, apply tighter internal controls, especially on the monitoring element, because any risk can occur.